2007
DOI: 10.1098/rspb.2007.0906
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of feeding behaviour in the thylacine and dingo as a novel test for convergence and niche overlap

Abstract: The extinct marsupial thylacine (Thylacinus cynocephalus) and placental grey wolf (Canis lupus) are commonly presented as an iconic example of convergence. However, various analyses suggest distinctly different behaviours and specialization towards either relatively small or large prey in the thylacine, bringing the degree of apparent convergence into question. Here we apply a powerful engineering tool, three-dimensional finite element analysis incorporating multiple material properties for bone, to examine me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(168 citation statements)
references
References 36 publications
6
161
1
Order By: Relevance
“…Here we further expand that 3D cranial dataset 6 by an additional 35 species, including members of Canis and Vulpes (the eutherian genera to which the thylacine is most commonly compared [46][47][48][49][50][51][52][53] ), dasyuromorphs and New World didelphids, 8 families of Diprotodontia (the clade containing carnivorous thylacoleonids but also kangaroos, wallabies, koalas, possums, gliders, and wombats), and other insectivorous australidelphids from the orders Microbiotheria, Notoryctemorphia and Peramelemorphia. The majority of newly added taxa are relatively small (0.1-5 kg body mass), representing the noncarnivorous marsupials to which the thylacine is most closely related (such as the southern marsupial mole Notoryctes typhlops and the eastern barred bandicoot Perameles gunnii).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we further expand that 3D cranial dataset 6 by an additional 35 species, including members of Canis and Vulpes (the eutherian genera to which the thylacine is most commonly compared [46][47][48][49][50][51][52][53] ), dasyuromorphs and New World didelphids, 8 families of Diprotodontia (the clade containing carnivorous thylacoleonids but also kangaroos, wallabies, koalas, possums, gliders, and wombats), and other insectivorous australidelphids from the orders Microbiotheria, Notoryctemorphia and Peramelemorphia. The majority of newly added taxa are relatively small (0.1-5 kg body mass), representing the noncarnivorous marsupials to which the thylacine is most closely related (such as the southern marsupial mole Notoryctes typhlops and the eastern barred bandicoot Perameles gunnii).…”
Section: Methodsmentioning
confidence: 99%
“…Species scores from the first 31 PC axes, accounting for 99% of the total morphological variation, were used as phenotypic variables. C 1 -C 3 were estimated for all pairwise comparisons between the thylacine and species of Canis and Vulpes, the two eutherian lineages which the thylacine most superficially resembles 46,47,50,51 . We also estimated convergence values between the thylacine and its closest carnivorous marsupial relatives, the extinct Nimbacinus dicksoni and Barinya wangala, as well as with the closely related insectivorous taxon, Myrmecobius fasciatus (Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…The application of loading is usually in the form of single force components representing entire muscle groups. More recent studies of skull loading have started to apply forces more widely over muscle attachment regions (e.g., Wroe et al, 2007;Grosse et al, 2007;McHenry et al, 2007). Whether single or several muscle forces are applied, muscle wrapping is rarely included, with only the most recent publications looking into its effects (Grosse et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In FEA of the cranium in which masticatory function is modeled, forces, either in terms of force vectors or force inducting elements, are applied to represent the action of muscles of mastication (e.g., Witzel et al, 2004;Ross et al, 2005;Witzel and Preuschoft, 2005;Strait et al, 2007;Wroe et al, 2007). The application of loading is usually in the form of single force components representing entire muscle groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that to date only jaw adducting (intrinsic) musculature has been considered in either in vivo or FE studies of stress/strain during feeding in the primate skull. It has been shown that extrinsic forces generated by cervical musculature can be relatively high in predatory mammals in the dispatch of small prey (Preuschoft and Witzel, 2005;Wroe et al, In Press) and Pan troglodytes is known to kill and eat other vertebrates (Anderson and Kitchener, 1983;Boesch, 1994).…”
Section: Discussionmentioning
confidence: 99%